LEGAL PROTECTION FOR LOSS OF MOTORBIKES IN THE PARKING LOT OF THE TOURISM CENTER OF CIREBON REGENCY BASED ON REGIONAL REGULATION NO.11 OF 2019 CONCERNING THE IMPLEMENTATION OF PARKING: (Case study in Bukit Cinta – Mundu, Cirebon Regency) - Andita Alfarisy, Panji; Marlina, Tina; Maulida, Irma (Fakultas Hukum Universitas Swadaya Gunung Jati, 2024)
Chapter 18, paragraph (1) of the Consumer Protection Law is included and regulated regarding the provisions for the Inclusion of Standard Clauses, where